Influence of enzymes and technology on virgin olive oil composition - Peres, Fátima (2018)
This work aims at presenting the state-of-the-art about the influence of the activity of olive endogenous enzymes, as well as of the application of adjuvants in olive oil technology, discussing their influence on the composition of virgin olive oil, especially in phenols and volatile compounds